Inflammatory cytokines kinetics define the severity and phase of nephropathia epidemica. (February 2015) - Baigildina, Asia A; Khaiboullina, Svetlana F; Martynova, Ekaterina V; Anokhin, Vladimir A; Lombardi, Vincent C; Rizvanov, Albert A
Aims: Nephropathia epidemica (NE) is a form of hemorrhagic fever with renal syndrome associated with the Puumala virus species of Hantavirus . The pathogenesis of NE is not well understood; therefore, investigating the inflammatory cytokine response to infection may provide useful knowledge in deciphering the pathophysiology of NE.Materials & methods: Using Luminex and ELISA, we analyzed the serum of 137 NE cases and 44 controls to investigate if serum cytokines associate with different clinical presentations.Results: Serum levels of TNF-α and IL-1β are associated with disease severity while upregulation of IL-6, CXCL10, CCL2 and CCL3 are associated with clinical presentation.Conclusion: Inflammatory cytokine kinetics associate with the severity and phase of NE. Our data support a role for inflammatory cytokines in the pathophysiology of NE.